Determination of Aflatoxins B1, B2, G1, and G2 concentrations in cheese puffs made from corn flour in Iran - Samrand Reshadi; Roshanak Daie Ghazvini; Seyed Jamal Hashemi; Heydar Bakhshi; Pegah Ardi; Nafiseh Shakibamehr; Mahdi Babaie; Shojaat Dashtipour; Zahra Rafat (Scientific Reports)
Abstract As a highly fundamental crop with a strategic role in human and animal nutrition, corn is frequently contaminated with mycotoxins. Mycotoxin contamination of corn poses substantial risks to human health. This study aimed to evaluate the concentration of aflatoxins levels in three popular brands of cheese puffs prepared from corn flour. This cross-sectional study was carried out on 27 specimens of cheese puffs produced by three famous brands. Aflatoxins were extracted from dry specimens with methyl alcohol. The obtained leachate was diluted with distilled water and subsequently passed through an HPLC column containing antibodies specific to B- and G-group aflatoxins. Finally, the obtained data were analyzed statistically using t-test and chi-squared test. The highest concentration of aflatoxins in brands A, B, and C was observed in specimens A1 (1.35 ng/mL), B2 (0.95 ng/mL), and C2 (1.22 ng/mL), respectively. Additionally, specimens A3 (0.93 ng/mL), B3 (0.80 ng/mL), and C1 (0.75 ng/mL) contained the lowest levels of aflatoxins among these brands, respectively. The results indicated that the concentration of aflatoxins was lower than the permissible limit in Iran (5 µg/kg) in all understudied specimens.